Implementasi Algoritma Jaro-Winkler dan Levenstein Distance dalam Pencarian Data pada Database - Yulianingsih Yulianingsih (Universitas Indraprasta PGRI Jakarta, 2017)
Data is a source of information that must be valued of contains true meaning which can be used or processed to benefit everyone need. Data can be found or searched in accordance with the needs thus required a good understanding of some search methods to get the right results. In this writing submitted the results of comparative testing using Levenshtein Distance and Jero-Winkler algorithm against a number of human name data which has a high degree of similarity. The purpose of this study is to determine one of two methods that have highest level of validation in search data that has a high similarity.Testing is done repeatedly and then carried out observations at each stage. Finding can be used as a basic for determining the appropriate method of use in data search.